TIRZEPATIDE - A NEW ERA IN OBESITY TREATMENT? A REVIEW OF THE CURRENT STATE OF KNOWLEDGE - Adam Solarz; Joanna Kryślak; Szymon Szabelski; Estera Graczyk; Maciej Sokołowski; Karolina Oskroba (International Journal of Innovative Technologies in Social Science, 2025)
Obesity represents a serious public health issue and is one of the main risk factors for cardiovascular, metabolic, and various oncological diseases. Modern therapies based on incretin-class drugs have attracted considerable interest due to their broad metabolic effects, including not only support in weight reduction but also improved glycemic control. Tirzepatide, a dual incretin receptor agonist, has demonstrated superior efficacy in promoting weight loss and maintaining a healthy body weight. Increasing evidence suggests that its clinical effectiveness exceeds that of traditional incretin therapies in multiple aspects. Adverse effects are most often mild and well tolerated, with no significant impact on patients’ quality of life. This makes tirzepatide a promising therapeutic option for individuals with obesity, both with and without concomitant diabetes. Despite encouraging results, further long-term, randomized, double-blind clinical trials are needed to confirm its efficacy and safety across diverse patient populations and to develop clear treatment protocols and dosage escalation strategies during therapy. Objective: A review of selected articles, literature, and the latest reports on the use of tirzepatide in the treatment of obesity. Materials and Methods: A literature review of scientific articles available on PubMed and Google Scholar.